KEEFEKTIFAN PEMBELAJARAN OUTDOOR LEARNING BERBASIS NILAI KARAKTER TERHADAP HASIL BELAJAR TEMATIK TERINTEGRASI SISWA KELAS IV SD NEGERI 1 METESEH REMBANG - Henry Januar Saputra; Anugerah Diah Novitasari (Universitas PGRI Semarang, 2014)
The background of this result use convensional method learning and the result of the study is under KKM65. The purpose of this result is to analyze the efectiveness of the outdoor learning base on character score toward the result of the study thematic integration students class IV elementary School 1 Meteseh Rembang. The experiment method that is used: quantitative experiment method. The experiment design that is used: pretest-posttest-control group design. The result of the study after treatment between a group of experiment that use outdoor learning and control group use convensional study have differences avarage result of the study. Co-efficient treatment-t is about 3,873 with the result of the study experiment group 80,11 with presentation completeness of the study classical 100%.Meanwhile the average result of the study control group is 70,22 with presentation completeness study clasical 77,78%. This can be conclude that outdoor learning study base on character score efective to increase the result of the study integrated thematic students class IV elementary school 1 Meteseh Rembang.